« Et encourt sont les dictes forches en la dicte place toutes droictes… ». La guerre des gibets dans l’État bourguignon naissant (Franche-Comté, 1380-1400) - Michelle Bubenicek (Criminocorpus)
Just as the signboards that physically mark the territory in the Prince’name, the gallows show the progression of his sovereign justice and his political authority. It is still necessary, however, that these markers are accepted and the forks left upright... This physical possession of the territory acquires a significance within a political space Under constitution, as could be the nascent the Bourgogne state. The county of Bourgogne – Franche-Comté – appears as the privileged ground of a « war gallows » between Philippe le Hardi , the first Duke Valois of Bourgogne, and some of his political opponents, great nobles and community inhabitants, as the imperial city of Besancon.